Cultural Multidimensionality in Research Practices - Uvarova, Tatiana (Journal of History Culture and Art Research, 2019)
The article considers multidimensionality as a new paradigmatic trend. The author touches the history of the emergence of the concept of multidimensionality within research practice, considers the multidimensionality of culture based on key concepts of the philosophy of multidimensionality. Culture as a complex and holistic system is an object of research, while the subject of research is multidimensionality of culture in the research practices. The article aims to demonstrate the research possibilities of cultural multidimensionality through key concepts of the philosophy of multidimensionality. The paper concludes that despite the widespread introduction of the multidimensionality ideas into the scientific discourse, multidimensionality of culture is not explicated from those positions. It is defined that there are terminological uncertainty and conceptual discord in definitions of multidimensionality. To a great extent, the term "multidimensionality" is used metaphorically. On the basis of multidimensionality philosophy, it is suggested to comprehend the ability to simultaneously measure a multitude of elements, applying various methods and various measurements, taking into account plurality of dimensions of culture, as a complex, self-organizing, nonlinear and holistic system. Accordingly, an approximation of philosophical reflection on multidimensionality with a multidimensional approach to cultural research is very promising. Multidimensionality uncovers various methodological possibilities, which, once discovered and applied, can serve as means of creation of more reliable approaches towards resolution of prominent theoretical problems in the field of culture.